Síntese e caracterização de nanofitas de óxido de estanho - Aguiar, Rosiana (Universidade Federal de São Carlos, 2004)
Tin oxide nanoribbons were synthesized by a carbothermal method, which is based on evaporation-condensation reactions. The source material was composed of commercial tin dioxide (SnO2) powders mixed with carbon black. This mixture was placed in the center of a tube furnace. The carbon reduces tin dioxide, resulting in tin oxide (SnO) vapor, which is carried to colder regions of the furnace, where condensation takes place and SnO2 nanoribbons are formed. During the synthesis, the furnace was heated up to 1250oC for 2 hours. The effect of the furnace atmosphere was also studied in this work. In this manner, one-dimensional tin oxide nanostructures with different oxidation states were obtained (SnO, Sn2O3 and SnO2). The samples were characterized by X-ray diffraction, scanning electron microscopy and transmission electron microscopy. It was possible to distinguish two growth mechanisms for the prepared nanostructures. The vapor-solid (VS) mechanism seems to be the most probable growth process for the SnO2 and Sn2O3 nanostructures. On the other hand, a self-catalytic vapor-liquid-solid (VLS) mechanism can be ascribed to the formation of SnO nanowires. Finally, a experimental procedure was developed to verify the possibility of preparing doped tin oxide nanoribbons. Antimony oxide (III) was added as a dopant in tin oxide powders by the oxide mixture method. The resultant material was mixed with carbon black and used as a source powder for the preparation of the doped nanostructures. The samples were analyzed by scanning electron microscopy, transmission electron microscopy and energy-dispersive X-ray spectroscopy. Although there are some evidence on the doping of the tin oxide nanoribbons with antimony, it was not possible to directly confirm it.
Sinthesys and Characterization of Tin Oxide Nanoribbons
Keywords: Material cerâmico; Crescimento de grãos; Cerâmica eletrônica; Nanomateriais; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA